Essay for hard days (Palíndromo, 2021)
Visual essay that uses iconic elements of a flight routine taking the portrait as a category-image of the subject and his shared feelings. Photographs that shows the urgency to find ways out. This work integrates research that relates photography to other artistic languages.
Keywords: photography; fotoperformance; series; portrait; studio.